Evaluation of sperm DNA quality in men presenting with testicular cancer and lymphoma using alkaline and neutral Comet assays. (26th September 2017) - Kumar, K.; Lewis, S.; Vinci, S.; Riera‐Escamilla, A.; Fino, M.‐G.; Tamburrino, L.; Muratori, M.; Larsen, P.; Krausz, C.
Summary: Despite more cancers in young men over the past two decades, improvements in therapies give a greater chance to live full lives following treatment. Sperm genomic quality is variable following cancer diagnosis, so its assessment is important if sperm cryopreservation is being considered. Here, we evaluated DNA damage using two DNA damage assays: an alkaline and for the first time, a neutral Comet assays in men presenting with testicular cancer ( n  = 19 for alkaline and 13 for neutral group) and lymphoma ( n  = 13 for alkaline and 09 for neutral group) compared with fertile donors ( n  = 20 for alkaline and 14 for neutral group). No significant differences were observed in any semen analysis parameters. In contrast, sperm DNA damage was higher in men with testicular cancer than in donors as assessed by both the alkaline (12.4% vs. 37.4%, p  < 0.001) and neutral (7.5% vs. 13.4%; p  < 0.05) Comet assays. Similar trends were observed in men with lymphoma. Here, sperm DNA damage was higher using both the alkaline (35.0% vs. 12.4%) and neutral (10.7% against 7.5% ( p  < 0.05) Comet assays. Moreover, the DNA strand breaks (particularly double‐strand breaks) were significantly more prominent in men with cancer having abnormal seminal parameters than normozoospermic ones. This study showed that sperm DNA testing using alkaline and neutral Comet assays is more sensitive than semen analysis in detecting impaired sperm quality in men presenting with cancer. It may provide a useful adjunct when considering storage prior to cancer investigations and assisted reproductive techniques (ART)‐based treatment.